ANALISIS KESEJAHTERAAN PETANI PADI SAWAH STUDI KASUS DI KECAMATAN NARMADA KABUPATEN LOMBOK BARAT - MADE SUMA WEDASTRA (SOSIAL SAINS DAN TEKNOLOGI, 2021)
This research is a descriptive study conducted in Narmada District, West Lombok Regency by taking a sample of 60 farmers, proportionally random sampling on the basis of the largest rice plant area in the 2020/2021 rainy season. Data collection methods are observation, documentation and interviews using questionnaire data collection tools. The data were analyzed by cost and profit analysis as well as the level of welfare of farmers based on the exchange rate of rice equivalent in rural areas.From the results of the study, it can be concluded that judging from the exchange rate of rice, lowland rice farmers in Narmada District are in the prosperous category, because the need for rice is 165.47 kg/family member per season, while the poverty line occurs in the need for rice which is smaller than 107 kg/season. season / family members. For other researchers, to analyze the level of welfare of farmers, it is analyzed using criteria according to the Central Statistics Agency (BPS) by looking at food and non-food needs.